Failure analysis and numerical simulation of slab carrying clamps (Fracture and Structural Integrity, 2020)
The goal of this study was to determine the reasons for failure of slab carrying clamps which had occurred in one of the clamp support levers. Detailed fractography analysis revealed that there was a welded joint at the location where failure occurred, which was not expected, since the second lever was not welded. Once the presence of the welded joint was confirmed by hardness measuring and the analysis of chemical composition, attempts were made to determine which materials were used for the welding, in order to obtain a more detailed insight into the nature of the failure. The first step of this extensive analysis involved the development of a simple, approximated numerical model, with the goal of determining the location of stress concentration in the support lever, so that it could be compared to the real failure location. Further investigations will involve more complex models, including the ones that will simulate crack growth, once its location is numerically verified.
Keywords: Failure; FEM analysis; Simulation; Welding influence; Fractography